AB1144 ULTRA HIGH FIELD MRI MICROARCHITECTURE ANALYSIS IMPROVES THE PREDICTION OF PROXIMAL FEMUR FRACTURE: A COMBINED STUDY WITH EX VIVO BIOMECHANICAL TESTS. (June 2019) - Guenoun, Daphne; Pithioux, Martine; Souplet, Jean-Christophe; Guis, Sandrine; Corroller, Thomas Le; Fouré, Alaxandre; Pauly, Vanessa; Mattei, Jean-Pierre; Bernard, Monique; Guye, Maxime; Chabrand, Patrick; Champsaur, Pierre; et al.
Abstract : Background: The purpose of this study was to assess cadaveric proximal femurs from the points of view of bone microarchitecture using ultra-high field (UHF) 7 Tesla magnetic resonance imaging (MRI), bone strength using biomechanical tests and bone mineral density (BMD) using Dual-energy X-ray absorptiometry (DXA). Objectives: We aimed at determining whether bone microarchitecture parameters were related to bone strength and BMD and whether UHF MRI can provide additional information regarding bone strength. Methods: BMD of ten proximal femurs from five cadavers were investigated using DXA and the bone volume fraction (BVF), trabecular thickness (Tb.Th), and trabecular spacing (Tb.Sp), fractal dimension (FD), Euler characteristics (Euler Ch.), Connectivity density (Conn. D) and Degree of anisotropy (DA) of each femur was quantified using UHF MRI. The whole set of specimens underwent mechanical compression tests to failure. Results: BMD and all the microarchitecture parameters except ConnD were significantly correlated with failure load (p < 0.05). The microarchitecture parameters were correlated to each other but not correlated with BMD. Multiple regression analysis demonstrated that the combination of the microarchitecture parameters and BMD improved the prediction of the failure load with for example an improved fracture risk prediction from R 2 = 0.418 to 0.688 when combining BMD and Euler Ch. Overall, femur bone microarchitecture assessed with UHF MRI was significantly correlated with biomechanical parameters. The multimodal assessment of BMD and trabecular bone microarchitecture using UHF MRI improved the fracture risk prediction of femoral bone and might be of interest for the future investigation of selected osteoporotic patients. Conclusion: We demonstrated that femur bone microarchitecture assessed with UHF MRI was significantly correlated with biomechanical parameters. The multimodal assessment of bone mineral density and trabecular bone microarchitecture using UHF MRI improved the fracture risk prediction of femoral bone and might be of interest for the future investigation of selected osteoporotic patients. Disclosure of Interests: None declared